Functional Analysis of Nuclear Estrogen Receptors in Zebrafish Reproduction by Genome Editing Approach - Lu, Huijie; Cui, Yong; Jiang, Liwen; Ge, Wei (Endocrinology (Philadelphia), 2017)
Estrogens signal through both nuclear and membrane receptors with most reported effects being mediated via the nuclear estrogen receptors (nERs). Although much work has been reported on nERs in the zebrafish, there is a lack of direct genetic evidence for their functional roles and importance in reproduction. To address this issue, we undertook this study to disrupt all three nERs in the zebrafish, namely esr1 (ERα), esr2a (ERβII), and esr2b (ERβI), by the genome-editing technology clustered regularly interspaced short palindromic repeats and its associated nuclease (CRISPR/Cas9). Using this loss-of-function genetic approach, we successfully created three mutant zebrafish lines with each nER knocked out. In addition, we also generated all possible double and triple knockouts of the three nERs. The phenotypes of these mutants in reproduction were analyzed in all single, double, and triple nER knockouts in both females and males. Surprisingly, all three single nER mutant fish lines display normal reproductive development and function in both females and males, suggesting functional redundancy among these nERs. Further analysis of double and triple knockouts showed that nERs, especially Esr2a and Esr2b, were essential for female reproduction, and loss of these two nERs led to an arrest of folliculogenesis at previtellogenic stage II followed by sex reversal from female to male. In addition, the current study also revealed a unique role for Esr2a in follicle cell proliferation and transdifferentiation, follicle growth, and chorion formation. Taken together, this study provides the most comprehensive genetic analysis for differential functions of esr1, esr2a, and esr2b in fish reproduction.The nuclear estrogen receptors (nERs)—esr1, esr2a, and esr2b—were deleted in the zebrafish. All mutant fish, including single, double, and triple mutants, were analyzed for phenotypes in reproduction.